FACTORS INFLUENCING NIGERIAN FARMERS’ ADOPTION OF SOLAR WATER PUMPS FOR AGRICULTURAL APPLICATION - Sani Ibrahim, Mohammed; Kumari R., Dr. Oum (The journal of contemporary issues in business and government, 2022)
Farmers in many countries have at their disposal several options to control their energy expenditures of agriculture. One available choice that the farmers have not extensively adopted is the technology of solar energy for generation of electricity. The main objective of this research work was to have an idea of thelevel of farmers’ adoption of solar-powered water pumps and the major factors that influence adoption behavior. The study therefore usedan extended UTAUT model to examine the adoption behavior of farmers regarding solar-powered pumps. A survey was used for the UTAUT model application. The study found that few farmers were found to use solar photovoltaic technology and solar equipment for farming. Decisions of farmers on adoption were found to be influenced by many factors including environmental change, economic benefits, government policies, awareness, costs of technology etc. It was observed that increasing the level of awareness and provision of government policies such as subsidies and incentives to reduce the costs of solar water pumps could increase farmers’ level of adoption. From the results, the authorsinfer that farmers’ lack of knowledge of new farming technologies and schemes resulted in some farmers not investing in solar-powered pumps.